Evaluation of a Psychoeducation Program Given to International Nursing Students for Healthy Lifestyle and Life Satisfaction - KAÇAN, Havva; ATEŞ, Sebahat (Marmara University, 2022)
Objective: This research was conducted to evaluate the effectiveness of a psychoeducation program given to international nursing studentsreceiving education in the nursing department of a public university to improve their healthy lifestyle behaviors and life satisfaction.Methods: The research was designed based on the single-group pretest-posttest model. The research sample consisted of 68 internationalstudents enrolled in the university’s nursing department in the 2016-2017 academic year. Data were collected using the introduction form,Healthy Lifestyle Behaviors Scale, and Life Satisfaction Scale. Pre-education and post-education scores were compared using the dependentt-test.Results: The total Healthy Lifestyle Behaviors Scale score and subscale scores significantly increased after the program (p≤0.001). The scoreobtained from the Life Satisfaction Scale was 20.1±4.6 before the program and 25.9±3.9 after the program, and this increase was statisticallysignificant (p≤0.001).Conclusion: The psychoeducation program given to international students effectively ensures that students gain healthy lifestyle behaviors,positively affecting life satisfaction.
Keywords: International student; International student; psychoeducation; healthy lifestyle; life satisfaction; nursing; Sağlık Kurumları Yönetimi; Healthy lifestyle; Nursing; Health Care Administration; Life satisfaction; Psychoeducation; 4. Education; 16. Peace & justice; 3. Good health; 10. No inequality